2020
DOI: 10.1002/csc2.20086
|View full text |Cite
|
Sign up to set email alerts
|

Systematic determination of the reproductive growth stage most sensitive to high night temperature stress in rice (Oryza sativa)

Abstract: High night‐temperature (HNT) stress during the reproductive stage of rice (Oryza sativa L.) reduces spikelet fertility and yield by inhibiting important physiological processes. However, specifics such as the period of time that is most sensitive to HNT, is unknown. To investigate this, we conducted four controlled‐environment experiments with two rice cultivars, N22 (HNT tolerant) and WAB56–104 (HNT susceptible). These cultivars were exposed to varying durations and intensities of night temperatures (control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
10
1
Order By: Relevance
“…Using empirical models and data from long‐term studies, the negative impact of increasing night temperatures on cereals across major cropping regions of the world has been documented (rice [ Oryza sativa L.]: Peng et al, 2004; Welch et al, 2010), wheat [ Triticum aestivum L.]: Lobell et al, 2005; Rao et al, 2015), and wheat and barley [ Hordeum vulgare L.]: Garcia et al, 2018). Experimentally, higher night temperatures inhibit growth and development, ultimately leading to lower grain yield and quality in field crops including rice (Bahuguna, Solis, Shi, & Jagadish, 2017; Coast, Sebela, Quinones, & Jagadish, 2020; Shi et al, 2013), wheat (Garcia, Dreccer, Miralles, & Serrago, 2015; Garcia, Serrago, Dreccer, & Miralles, 2016; Hein et al, 2019; Impa et al, 2019, 2020; Prasad, Pispati, Ristic, Bukovnik, & Fritz, 2008), barley (Garcia et al, 2015, 2016) and maize ( Zea mays L.; Y. Wang et al, 2019). Because of the asymmetry in warming, increasing maximum day temperatures leading to short episodes of heat spikes could impact crop yields differently across locations (Gourdji, Sibley, & Lobell, 2013), while increasing minimum night temperature could impact wider geographic regions with sustained warming for longer time frames (Cox, Maclean, Gardner, & Gaston, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using empirical models and data from long‐term studies, the negative impact of increasing night temperatures on cereals across major cropping regions of the world has been documented (rice [ Oryza sativa L.]: Peng et al, 2004; Welch et al, 2010), wheat [ Triticum aestivum L.]: Lobell et al, 2005; Rao et al, 2015), and wheat and barley [ Hordeum vulgare L.]: Garcia et al, 2018). Experimentally, higher night temperatures inhibit growth and development, ultimately leading to lower grain yield and quality in field crops including rice (Bahuguna, Solis, Shi, & Jagadish, 2017; Coast, Sebela, Quinones, & Jagadish, 2020; Shi et al, 2013), wheat (Garcia, Dreccer, Miralles, & Serrago, 2015; Garcia, Serrago, Dreccer, & Miralles, 2016; Hein et al, 2019; Impa et al, 2019, 2020; Prasad, Pispati, Ristic, Bukovnik, & Fritz, 2008), barley (Garcia et al, 2015, 2016) and maize ( Zea mays L.; Y. Wang et al, 2019). Because of the asymmetry in warming, increasing maximum day temperatures leading to short episodes of heat spikes could impact crop yields differently across locations (Gourdji, Sibley, & Lobell, 2013), while increasing minimum night temperature could impact wider geographic regions with sustained warming for longer time frames (Cox, Maclean, Gardner, & Gaston, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These comparable results in both agronomic and quality parameters from growth chambers, small field-based enclosures and large field-based experiments reveal consistent effects of HNT in a variety of testing environments. Having demonstrated the agreement of findings across controlled environments and field conditions, provides new avenues to use high throughput phenotyping indices identified under chamber conditions 14 . Extending chamber based indices will facilitate effective utilization of advances in phenotyping to large scale field infrastructure involving diversity panels and mapping populations.…”
Section: Resultsmentioning
confidence: 86%
“…This increase in global mean surface temperature is being driven by an increase in the average daily minimum temperature, which is rising at a quicker rate than the average daily maximum temperature [5][6][7][8] . Studies related to high night temperature (HNT) stress on different crops have increased recently (between 2010 and 2020) with many of these focused on rice [9][10][11][12][13][14][15] . A comprehensive study conducted at the International Rice Research Institute in the Philippines showed that the mean maximum temperature between 1979 and 2003 rose by 0.35 °C while the annual mean minimum temperature rose by 1.13 °C.…”
mentioning
confidence: 99%
“…Recent research assessing the potential impacts of high night air temperature on rice yield had focused on constant air temperature treatments that were set to produce significant outcomes (i.e. Tamaki et al, 1989;Cooper et al, 2008;Coast et al, 2019). These studies had, for the most part, treated each trait of rice yield potential without relation to actual changes in air temperature under local rice environments.…”
Section: Night-time Air Temperature Pattern In the Four Rice Producinmentioning
confidence: 99%